2019
DOI: 10.1039/c9mh00765b
|View full text |Cite
|
Sign up to set email alerts
|

Revisiting the charge compensation mechanisms in LiNi0.8Co0.2−yAlyO2 systems

Abstract: The emergence of oxidized oxygen RIXS features at high voltages for Ni-rich layered oxide cathodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
89
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 72 publications
(97 citation statements)
references
References 78 publications
6
89
1
Order By: Relevance
“…These results further strengthen the reductive coupling scenario about the important role of TM-O interaction in oxygen redox systems, which is critical for the ultimate understanding of the mechanism of lattice oxygen redox reactions, something remains a grand challenge in the field and require further intensive studies. Another finding from our mRIXS results is the reversible lattice oxygen redox in such a conventional layered LiNiO 2 , which has very few direct experimental evidences, 32,36,[52][53][54] although the overall contribution is relatively small in the mRIXS maps were collected in the ultra-high efficiency iRIXS endstation at Beamline 8.0.1 at the Advanced Light Sources (ALS). 57 Sample surface was mounted 45° to the incident beam, and the outgoing photon direction along the RIXS spectrograph is 90° with other technical details available in our previous report.…”
Section: The Redox Chemistry Of Linio 2 Is Seemingly Straightforwardmentioning
confidence: 99%
“…These results further strengthen the reductive coupling scenario about the important role of TM-O interaction in oxygen redox systems, which is critical for the ultimate understanding of the mechanism of lattice oxygen redox reactions, something remains a grand challenge in the field and require further intensive studies. Another finding from our mRIXS results is the reversible lattice oxygen redox in such a conventional layered LiNiO 2 , which has very few direct experimental evidences, 32,36,[52][53][54] although the overall contribution is relatively small in the mRIXS maps were collected in the ultra-high efficiency iRIXS endstation at Beamline 8.0.1 at the Advanced Light Sources (ALS). 57 Sample surface was mounted 45° to the incident beam, and the outgoing photon direction along the RIXS spectrograph is 90° with other technical details available in our previous report.…”
Section: The Redox Chemistry Of Linio 2 Is Seemingly Straightforwardmentioning
confidence: 99%
“…However, later studies clarified that Li2IrO3 does not have ORR unless doped with Sn, and voltage hysteresis unfortunately gets strong while ORR emerges in the Sn doped Li2IrO3 systems. 18 Secondly, very recent reports have revealed that non-Li-rich conventional layered compounds display ORR at high voltages too [19][20][21] . These findings benefit from recent advances of O-K highefficiency mapping of resonant inelastic X-ray scattering (mRIXS), which could reliably detect the lattice (non-released) ORR in battery electrodes at charged states.…”
Section: Toc Graphicsmentioning
confidence: 99%
“…22 Other conventional Naion materials were also found to feature strong ORR, 23,24 but the Mg dopants are highly ionic and actually mimic the chemical environment to oxygen as alkali metals, i.e., the case alike Li-rich compounds. Anyway, although all these non-alkali-rich compounds with ORR display generally improved voltage hysteresis behaviors compared with Li-rich compounds, the ORR itself takes place at high voltages, which always leads to strong voltage hysteresis and highly irreversible reactions [19][20][21] .…”
Section: Toc Graphicsmentioning
confidence: 99%
“…With these merits, XAFS has been extensively applied for NRLO research. [ 75 ] Generally, the experimental setup and cell design from the above in situ/operando XRD test can also be applied to in‐place and real‐time XAFS measurements.…”
Section: Multiscale Characterizations Of Nrlo Degradationmentioning
confidence: 99%
“…[ 81 ] Besides sXAS, the resonant inelastic X‐ray scattering (RIXS) becomes popular recently to detect the anionic oxygen redox in batteries due to its good chemical sensitivity. [ 75,84 ] The RIXS fingerprint of oxygen redox is a sharp feature at approximately 523.8 eV emission energy. [ 75,84 ] The principle and application of RIXS in detecting oxygen redox can be found in another review.…”
Section: Multiscale Characterizations Of Nrlo Degradationmentioning
confidence: 99%